Usuários da Informação e Diversidade - Casarin, Helen de Castro Silva (Editora Oficina Universitária, 2021)
Following the theme of the previous book "Studies of Information Users", published in 2014, this work brings together texts by specialists from different areas of knowledge that present the main characteristics and information about people with different profiles. However, unlike the previous work, which brought information about the most recurrent groups of users in the literature, this book opted for a more inclusive and plural approach, including chapters on groups little addressed in works on the subject, such as babies, disabled , individuals with high abilities, people from the LGBTQIA+ group, users of archives and museums. The aim is to provide basic but fundamental information so that information professionals can understand the main characteristics and needs of these groups, eliminating preconceptions and stigmas that may compromise the work of librarians, archivists and museologists in assisting these individuals. The inappropriate or mistaken attitude of these professionals, often due to lack of knowledge about the specificities of these individuals, can unintentionally result in negative experiences for the user who, in turn, will have a distorted image of the role of professionals and Information Units, pushing him away or making it difficult to use the information units. In addition, these groups are often invisible to the work of professionals who are in charge of information units, remaining in the category of potential users or even non-users, since they themselves often do not recognize themselves as such and because they often the information units are not properly prepared to serve them.